Hepatoprotective effect of Solanum anomalum leaf on doxorubicin-induced hepatotoxicity in male rats - Oyepata Simeon Joseph (Shahrekord University of Medical Sciences, 2024)
Background and aims: Solanum anomalum Thonn. ex Schumach (Solanaceae) parts are used locally in ethnomedicine to treat various diseases. This work investigated the hepatoprotective potential of the S. anomalum to validate its ethnomedicinal uses and give scientific proof to its claimed antidotal activity in folkloric medicine. Methods: The hepatoprotective activity of S. anomalum leaf extract (70-210 mg/kg) was investigated against doxorubicin (DOX)-induced liver injury in rats. Rats were divided into five groups of six rats each and treated concomitantly with DOX (2.5 mg/kg i.p) and leaf extract (70, 140, and 210 mg/kg orally) for 14 days. Vitamin C was used as a standard drug. Liver function indices, liver enzymatic and nonenzymatic antioxidants, malondialdehyde (MDA) level, and histological assessment of the liver were determined to assess the hepatoprotective potentials of the extract. Results: DOX elevated liver function indices (AST, ALT, ALP, total and direct bilirubin) significantly (P < 0.05). These parameters were markedly reduced by coadministration of the leaf extract (70-210 mg/kg) (P < 0.05-0.01) when compared to the DOX-only group. Also, the extract coadministration improved total protein and albumin levels, which were reduced by DOX. Moreso, levels of reduced glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) that were decreased by DOX were significantly (P < 0.01) elevated by the leaf extract. In contrast, the raised MDA level was reduced. The DOX-only group had severe pathological features in its histological liver section, which were comparably reduced in the extract-treated groups. The histopathological changes corroborate other biochemical parameters determined, thus indicating hepatoprotective solid activity. Conclusion: This study's findings suggest that the leaf extract of S. anomalum possesses liver protective potentials, which may be due to the antioxidant activities of its phytochemical constituents. This property can be exploited in the treatment of DOX-related toxicities.